COMPARATIVE ANALYSIS OF REAL-TIME LOAD TRACKING TECHNOLOGIES: COMPARATIVE ANALYSIS OF REAL-TIME LOAD TRACKING TECHNOLOGIES - Antonov, Anton (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Real Time Locating Systems (RTLS) and Radio Frequency Identification (RFID) are key technologies in asset tracking and management. Although they may look similar at first glance, they have different characteristics, advantages and disadvantages that make them suitable for different applications.